Ultrastructure of microtriches on the scolex of Cyathocephalus truncatus (Cestoda: Spathebothriidea) - Levron, Céline; Scholz, Tomáš; Dezfuli, Bahram S (Folia parasitologica, 2008)
The scolex surface of the mature spathebothriidean Cyathocephalus truncatus (Pallas, 1781), a parasite of the brown trout Salmo trutta fario L., was studied using scanning and transmission electron microscopy. A particular attention was paid to microtriches, unique structure on the surface of the Cestoda. The scolex of C. truncatus is covered with two types of filiform microtriches (filitriches): aciculate (approximately 3 microm long) and capillate (approximately 10 microm long). Capillate microtriches, which have never been reported in any other spathebothriideans, are described for the first time using transmission electron microscopy. The tegument covered with filiform microtriches only (no spiniform microtriches are present) is typical of cestode groups supposed to be the most basal, e.g., Gyrocotylidea, Spathebothriidea, and Caryophyllidea.
Keywords: nervové receptory; Sensory Receptor Cells; Animals; Microscopy, Electron, Transmission; Italy; Trout; zvířata; pstruh; mikroskopie elektronová rastrovací; Microscopy, Electron, Scanning; transmisní elektronová mikroskopie; Itálie; Cestoda